STUDI KELAYAKAN INDUSTRI KECIL BARANG DARI ALUMINIUM DI KECAMATAN TAMPAN KOTA PEKANBARU - Siti Chairani; Wahyu Hamidi; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The alumunium industry is an of individuals who enganed in the processing of alumunium into items that are needed by the community, both for household, government agencies and the general environment. Many items that can be generated from this industrywith a variety of interesting shapes.The purpose of this study as to determine the feasibility of industrial goods of alumunium in the Tampan district in Pekanbaru cityd if viewed from the aspect of the market. Analyzing market demand forecasting with time series method, that is : linear trend, quadratic trend,exponential trend.Result from this study indicate the estimated demand goods of alumunium in thirty nine industries experiencing increased every month, demand din December 2014 showed the number of 780 units, while for the next month is January 2015 shows at 902,73 units, demand foredcasts up to December 2015 show in increase every month. That mean the industry has good prospects for development if viewed rom the aspect of the market.Keywords : Aspect of the market, prospective consumers,and demand forecast